Imaniya and Young Muslim Women in Côte d'Ivoire - LeBlanc, Marie Nathalie (Anthropologica, 2022)
In the 1990s, Muslims in Cote d'lvoire redefined the boundaries of their identity, as well as the structure of their community. While young men have been at the forefront of this movement of religious revitalization as leaders and erudites, the life trajectories of young Muslim women have been deeply altered by these changes. This article explores how, through renewed acts of faith and displays of orthodoxy, Western-style educated and financially self-sufficient young women are negotiating their participation into marriage markets. Their relatively new social roles, defined by Western-style education and salaried employment, exclude them from locally sanctioned notions of "proper womanhood." Whilst their lifeworld inscribes them within a locally defined space of modernity and self-realization, they are not fully actualized as Muslim women due to their exclusion from marriage markets and, by extension, legitimate motherhood. Through their overt display of Islamic practice and their participation into newly created Islamic youth associations, they position themselves as "marriageable women" in light of marriage practices that generally favour younger and less formally educated women. The locally articulated Arabized version of Islam is at the core of their inclusion into local and transnational matrimonial markets.